Numerical investigation of the influence of pulse frequency on the weld pool size in pulsed current TIG welding - Shahid Parvez; Magdy El Rayes; Essam Al-Bahkali; Khalid Alqosaibi (AIP Advances)
This study simulates the pulsed current tungsten inert gas (TIG) welding process to investigate the transient development of the weld pool in a 4 mm thick aluminum sheet, focusing on the effects of pulse frequency on the weld pool size. Two pulsed currents, 230 and 180 A, with a 30% background current, were examined. The 230 A current achieved full, while the 180 A resulted in partial penetration. Five pulse frequencies (1, 4, 10, 20, and 50 Hz) were analyzed. A numerical model was developed to compute heat and current fluxes on the workpiece surface. The arc profile shifted from a bell shape in high-frequency cycles to a conical shape in low-frequency cycles. The heat and current fluxes served as inputs to another model that simulated weld pool behavior for both direct and pulsed current TIG welding. The results showed that weld pool size decreased in pulsed current TIG welding. At 230 A, full penetration changed to partial penetration under pulsed current. At 1 Hz, sufficient time was available for solidification during the low-cycle period, but at 50 Hz, the weld pool remained liquid. As pulse frequency increased from 1 to 50 Hz, the weld pool depth decreased significantly, with a reduction from 2.4 to 0.9 mm at 230 A and from 1.1 to 0.34 mm at 180 A. Convection in the weld pool was influenced by temperature and was strongest at higher temperatures. The decrease in weld pool size was most pronounced between 1 and 10 Hz, stabilizing between 20 and 50 Hz. Validation against experimental macrographs demonstrated good agreement with the simulations.